FRI0277 Cardiovascular risk assessment in patients with ankylosing spondilytis: Comparison of three indexes and related variables. (23rd January 2014) - Magro-Checa, C.; Rosales-Alexander, J.L.; Montes-García, S.; Salvatierra, J.; Cantero-Hinojosa, J.; Sánchez-Parera, R.; Raya-Άlvarez, E.
Abstract : Background: EULAR task force recommendations in the cardiovascular (CV) risk were published in 2010. EULAR recommends the use of the SCORE when no local guidelines are available. In our country, two charts have been calibrated and are widely used to calculate cardiovascular mortality at 10 years, the SCORE table, calibrated by the National Cardiology Society (cSCORE) and the Framingham-Wilson score (REGICOR). Objectives: To assess the CV risk in Ankylosing Spondilytis (AS) patients (pts) using the SCORE for low risk European countries (eSCORE) and compare it with the cSCORE and the REGICOR. Furthermore, we analyzed the correlation of several clinical and serological variables with these indexes, and the percentage of high and very high CV risk pts receiving an adequate therapy for its management, coxibs and/or NSAIDs. Methods: This cross-sectional study included 103 consecutive pts who fulfilled the modified New York criteria for AS followed in our outpatient clinics. Patients with a previous CV event and diabetics were excluded. The following data were recorded for logistic regression analysis: sex, age, body mass index, classic CV risk factors, lipid profile, duration in months since diagnosis, clinical patterns of the AS, treatment, and inflammatory markers (p<0.05 was considered significant). The eSCORE function model, the cSCORE and the REGICOR were compared. According to our national guidelines, a high CV risk has been defined by a SCORE ≥5% and REGICOR ≥10%, the cutoff point recommended to start treatment. Results: Based on the classic CV risk factors, the eSCORE was 1, 78±2, 55% (mean ± standard deviation) and 11 pts (10, 67%) were above the threshold of high or very high CV risk (≥5%). After applying the cSCORE the values were 2, 87±3, 78% and with REGICOR were 4, 72±4, 36%. Therefore, 24 pts (23, 3%) and 12 pts (11, 65%) were reclassified above the threshold respectively. Multivariate regression analysis showed that the most important prognostic factor for predicting the cSCORE was the duration in months since diagnosis (p<0, 05) followed by ESR (p<0, 05). Analyzing the percentage of high and very high risk pts receiving adequate therapy for the CV risk management, based on the eSCORE 36, 3% of pts were treated adequately. When pts were reclassified with cSCORE, this percentage was 33, 3%, and with REGICOR 41, 6%. The percentage of high and very high risk pts receiving coxibs and NSAIDs was 72, 72% (eSCORE), 79, 16% (cSCORE) and 66, 66% (REGICOR). Conclusions: Assessment of the CV risk in AS pts applying the eSCORE and REGICOR leads to an underestimation of the CV risk, which have an impact on the correct management of these pts. Duration in months since diagnosis and ESR were prognostic factors of the cSCORE, what suggests that sustained inflammation could play a role in the increase of CV risk. Although EULAR recommends caution about prescribing coxibs and NSAIDs in high and very high risk pts, a high percentage of pts received these therapies. References: Peters MJL et al. EULAR evidence-based recommendations for cardiovascular risk management in patients with rheumatoid arthritis and other forms of inflammatory arthritis. Ann Rheum Dis. 2010;69:325–331 Disclosure of Interest: None Declared